Sam Tractor to the rescue - Baxter, Nicola; Burnett, Alex, illus (London : Ladybird)
When a big storm xloses in, Sam tractor tries to get the farm animals to safety. But the animals won't listen to Sam.
Keywords: Farm life. -- Fiction; Strom -- Fiction; Tractors -- Fiction